The Role of Principal Learning Supervision on Teacher Performance - Sulistiana, Tati; Wiyono, Bambang Budi; Imron, Ali (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Academic supervision is one of the important strategies in supporting the improvement of professional, reflective, and competitive teacher performance. However, supervision is often perceived as administrative control rather than professional development, resulting in resistance and lack of impact on learning quality. This study aims to systematically examine the effect of principal supervision on teacher performance and the factors that support and hinder its effectiveness. Using the Systematic Literature Review (SLR) method, the authors analyzed 36 scientific documents selected through a PRISMA-based selection process from 400 initial sources. The literature was thematically analyzed to identify patterns of relationships between supervision strategies, principals' roles, and teacher performance outcomes. The results show that reflective, dialogic, and participatory supervision improves teachers' pedagogical, professional, social, and personality competencies. The findings also indicate that principals' main supporting factors are competence, collaborative culture, and policy support. In contrast, administrative burden, teacher resistance, and lack of training were significant barriers. This study emphasizes the importance of strengthening the principal's role as a professional coach and the need for a more contextualized and humanistic supervision policy reform. Academic supervision designed with an empowerment approach can be the foundation for building a sustainable and quality-oriented school culture.